Multi-Path Optimization for Efficient Production of 2′-Fucosyllactose in an Engineered Escherichia coli C41 (DE3) Derivative - Ni, Zhijian; Li, Zhongkui; Wu, Jinyong; Ge, Yuanfei; Liao, Yingxue; Yuan, Lixia; Chen, Xiangsong; Yao, Jianming (Frontiers in Bioengineering and Biotechnology, 2020)
2′-fucosyllactose (2′-FL), one of the simplest but most abundant oligosaccharides in human milk, has been demonstrated to have many positive benefits for the healthy development of newborns. However, the high-cost production and limited availability restrict its widespread use in infant nutrition and further research on its potential functions. In this study, on the basis of previous achievements, we developed a powerful cell factory by using a lacZ-mutant Escherichia coli C41 (DE3)ΔZ to further increase 2′-FL production by feeding inexpensive glycerol. Initially, we co-expressed the genes for GDP-L-fucose biosynthesis and heterologous α-1,2-fucosyltransferase in C41(DE3)ΔZ through different plasmid-based expression combinations, functionally constructing a preferred route for 2'-FL biosynthesis. To further boost the carbon flux from GDP-L-fucose toward 2'-FL synthesis, deletion of chromosomal genes (wcaJ, nudD and nudK) involved in the degradation of the precursors GDP-L-fucose and GDP-mannose were performed. Notably, the co-introduction of two heterologous positive regulators, RcsA and RcsB, was confirmed to be more conducive to GDP-L-fucose formation and thus 2′-FL production. Further a genomic integration of an individual copy of α-1,2-fucosyltransferase gene, as well as the preliminary optimization of fermentation conditions enabled the resulting engineered strain to achieve a high titer and yield. By collectively taking into account the intracellular lactose utilization, GDP-L-fucose availability, and fucosylation activity for 2'-FL production, finally a highest titer of 2′-FL in our optimized conditions reached 6.86 g/L with a yield of 0.92 mol/mol from lactose in the batch fermentation. Moreover, the feasibility of mass production was demonstrated in a 50-L fed-batch fermentation system in which a maximum titer of 66.80 g/L 2'-FL was achieved with a yield of 0.89 mol 2'-FL/mol lactose and a productivity of approximately 0.95 g/L/h 2'-FL. As a proof of concept, our preliminary 2'-FL production demonstrated a superior production performance, which will provide a promising candidate process for further industrial production.